Genera Encyrtidarum regionis palaearcticae. Auctoribus. - Erdös, József; Novický, Svaboslav (Contributions to Entomology = Beiträge zur Entomologie, 1955)
Nomenclatural ActsCercobelini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.Copidosomini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.Habrolepini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.Leptomastidini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.Microterini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.Pseudorhopini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.Trechnitini Erdös & Novicki, 1955 (Arrhenophaginae), trib. n.luctuosus Erdös & Novicki, 1955 (Athesmus), spec. n.anomalus Erdös & Novicki, 1955 (Birous), spec. n.Athesmus Erdös & Novicki, 1955 (Encyrtidae), gen. n.Birous Erdös & Novicki, 1955 (Encyrtidae), gen. n.Ginsiana Erdös & Novicki, 1955 (Encyrtidae), gen. n.Leiocyrtus Erdös & Novicki, 1955 (Encyrtidae), gen. n.Platyencyrtus Erdös & Novicki, 1955 (Encyrtidae), gen. n.obscura Erdös & Novicki, 1955 (Ginsiana), spec. n.clavatus Erdös & Novicki, 1955 (Leiocyrtus), spec. n.esuriens Erdös & Novicki, 1955 (Platyencyrtus), spec. n.